Siliceous slag mixture for pavement base layer and construction method of siliceous slag mixture
By combining siliceous slag, gravel and cement-based composite cementitious materials into siliceous slag mixture, and using specific construction methods, the problem of low utilization of siliceous slag is solved, efficient utilization of solid waste slag resources is achieved, and the strength and stability of the pavement base layer is improved.
Patent Information
- Application Number
- CN202510070520.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The low utilization rate of siliceous slag leads to the inadequate utilization of solid waste slag resources and the risk of environmental pollution.
By combining silica slag, gravel and cement-based composite cementitious materials into silica slag mixture, and using two-stage mixing, paving, rolling and curing construction methods, it is used for the construction of pavement base.
It realizes efficient utilization of silicon slag, reduces the use of cement, improves the strength and stability of the pavement base, meets the use requirements of highways above level 2, and promotes the resource utilization of solid waste slag.
Smart Images

Figure BDA0005245574240000071 
Figure BDA0005245574240000072 
Figure BDA0005245574240000081
Abstract
Description
Technical Field
[0001] The invention relates to a siliceous slag mixture for a road surface base and a construction method thereof. Background Art
[0002] At present, the discharge of solid waste residue is large but the utilization rate is low, which has led to many difficult problems. A large amount of solid waste residue that is not properly managed is like a potential "geological bomb", which significantly increases the risk of disasters such as slag pile collapse, posing hidden dangers to the surrounding environment and residents' safety. However, solid waste residue is not worthless. For example, siliceous slag is mainly composed of compounds formed by the combination of silicon, calcium and other chemical elements. It is formed during the metallurgical process and usually contains alumina and alkali. The ingredients make it chemically active and can play an important role in industrial production. It contains iron between 7-8%, aluminum about 8%, calcium about 12%, and moisture content maintained at about 6%. It has a certain hardness and is suitable for use as an abrasive or filling material in industrial applications.
[0003] Therefore, in view of the environmental problems caused by solid waste residue and its potential utilization value, Chinese patent CN1012951B discloses a method for producing cement using high-calcium fly ash, wherein the prepared cement is ground to a 0.08 mm square hole sieve with a sieve residue of less than 12%, and 5% to 30% (by weight) of potential hydraulic materials and volcanic ash materials are compounded when grinding cement clinker and high-calcium fly ash. Among them, volcanic ash includes siliceous slag. It can be seen that siliceous slag is generally used as an auxiliary material, and its usage is very small. Therefore, it is urgent to explore a method for using siliceous slag in large quantities to realize the resource utilization of solid waste residue, while reducing environmental pollution, creating considerable economic and social benefits. Summary of the invention
[0004] The invention aims to solve the problem of low utilization rate of siliceous slag and provides a siliceous slag mixture for a road surface base and a construction method thereof.
[0005] The technical method of the present invention is as follows:
[0006] A siliceous slag mixture for a road surface base comprises siliceous slag, crushed stone and cement-based composite cementitious material; wherein the cement-based composite cementitious material comprises cement, coal furnace slag from a thermal power plant and limestone powder.
[0007] Specifically, the mass ratio of the siliceous slag, crushed stone and cement-based composite cementitious material is 35-40:55-60:5-10.
[0008] Specifically, the mass ratio of the cement, coal furnace slag from a thermal power plant and limestone powder is 2-3:1:2-3.
[0009] Specifically, the crushed stones have three particle sizes, including 5-10 mm, 10-20 mm and 20-30 mm, wherein the mass ratio of the crushed stones of 5-10 mm, 10-20 mm and 20-30 mm is 5-10:40-45:5-10.
[0010] The present invention also provides a construction method for a road surface base, which comprises: performing two-stage mixing, paving, rolling and curing of a siliceous slag mixture.
[0011] Specifically, the two-stage mixing step includes: the siliceous slag mixture sequentially enters two mixing tanks connected in series, and is mixed in the mixing tanks, and the mixing time is not less than 15 seconds.
[0012] Specifically, the paving step includes: spreading the two-stage mixed mixture through a paver, wherein the paving speed is 1.0-3.0 m / min, the vibration frequency of the vibrator in the paver shall not be lower than 30 Hz, the impact frequency of the rammer shall not be lower than 20 Hz, and the stroke shall not be lower than 6 mm.
[0013] Specifically, the rolling steps include: rolling the paved mixture once with double steel wheels; during the rolling process, the double steel wheels do not vibrate when moving forward and vibrate when moving backward; rolling once with a single steel wheel, during the rolling process, the single steel wheel vibrates; kneading and rubbing with a rubber wheel that is greater than 30t; and finishing with double steel wheels.
[0014] Specifically, the curing is carried out by film covering or geotextile curing, and the curing time is not less than 7 days.
[0015] The beneficial effects of the present invention are:
[0016] 1. The present invention combines siliceous slag, crushed stone and cement-based composite cementitious materials into a siliceous slag mixture, wherein the cement-based composite cementitious materials include cement, coal furnace slag from thermal power plants and limestone powder. Siliceous slag has hydration and gelling properties, and can replace most of the cement, thereby reducing the amount of cement used; crushed stone improves the strength of the road base; the cement in the cement-based composite cementitious material can further strengthen the gelling, the coal furnace slag from thermal power plants in the cement-based composite cementitious material is active and can react with cement to promote solidification, and the limestone powder in the cement-based composite cementitious material can react with cement to promote solidification, and can also improve the working performance of the mixture, making it easier to construct and shape, thereby improving the overall stability of the road base to ensure its use on highways above level 2.
[0017] 2. The siliceous slag of the present invention is the waste slag discharged from the production of alum, and the coal furnace slag is the waste slag from the thermal power plant. By applying the above waste slag to the construction of the road surface base, the recycling of resources is achieved. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The present invention provides a siliceous slag mixture for a road surface base, wherein the siliceous slag mixture comprises siliceous slag, crushed stone and cement-based composite cementitious material, wherein the cement-based composite cementitious material comprises cement, coal furnace slag from a thermal power plant and limestone powder.
[0020] In one embodiment, the siliceous slag contains a large amount of spodumene, which is mainly composed of silicon oxide (SiO2) and aluminum oxide (Al2O3). These components give the siliceous slag potential hydration and gelling properties, that is, after adding water, a chemical reaction occurs at room temperature to generate a hydration product with gelling properties. Therefore, the siliceous slag is a volcanic ash mixed material with good activity and is suitable as a road base material. Here, the water content of the siliceous slag is relatively low, about 10%, and can be directly used as a raw material for making road base materials.
[0021] In one embodiment, the particle size of the siliceous slag is preferably ≤3mm, and the residue at the 0.045mm (i.e. 45μm) sieve hole is 39.1%, the pass rate is 60.9%, and the residue at the 0.080mm (i.e. 80μm) sieve hole is 25.2%, that is, the pass rate is 74.8%, which meets the 0.075mm pass rate required by the specification and meets the fineness requirement. The moisture content of the siliceous slag is preferably ≤20%.
[0022] In one embodiment, the particle size of the coal slag from a thermal power plant is 1-3 mm, and the coal slag from a thermal power plant is selected from a thermal power plant.
[0023] In one embodiment, the limestone powder is fine limestone powder, and the particle size of the limestone powder is 1-10 mm.
[0024] The present invention combines siliceous slag, crushed stone and cement-based composite cementitious materials into a siliceous slag mixture, wherein the cement-based composite cementitious materials include cement, coal furnace slag from a thermal power plant and limestone powder. Siliceous slag has hydration and gelling properties, and can replace most of the cement, thereby reducing the amount of cement used; crushed stone improves the strength of the road base; the cement in the cement-based composite cementitious material can further strengthen the gelling, the coal furnace slag from the thermal power plant in the cement-based composite cementitious material is active and can react with cement to promote solidification, and the limestone powder in the cement-based composite cementitious material can react with cement to promote solidification, and can also improve the working performance of the mixture, making it easier to construct and shape, thereby improving the overall stability of the road base to ensure use on highways above level 2.
[0025] In one embodiment, the mass ratio of siliceous slag, crushed stone and cement-based composite cementitious material is 35-40:55-60:5-10. Preferably, the mass ratio of siliceous slag, crushed stone and cement-based composite cementitious material is 38:57:5. This ratio is to ensure the strength requirements of the pavement base. If it is lower than this ratio, the pavement base cannot meet the standards of a first-class highway. If it is higher than this ratio, the pavement base can meet the standards of a first-class highway, but it will cause unnecessary waste.
[0026] In one embodiment, for example, the mass ratio of cement, coal slag from thermal power plants and limestone powder is 2-3:1:2-3. For example, the ratio may be 1:1:1, 1:2.5:1, 2:1:2.5, 2.5:1:2, etc.
[0027] In one embodiment, the crushed stone has three particle sizes. Specifically, the particle sizes include 5-10 mm, 10-20 mm and 20-30 mm. Here, the mass ratio of 5-10 mm crushed stone, 10-20 mm crushed stone and 20-30 mm crushed stone is 5-10:40-45:5-10, preferably, the mass ratio of 5-10 mm crushed stone, 10-20 mm crushed stone and 20-30 mm crushed stone is 7:41:9. Here, when crushed stones of different particle sizes are laid on the road surface, a compact structure can be formed through gradation design, thereby improving the bearing capacity and stability of the road surface. For example, 5-10 mm crushed stone can provide better compactness and drainage performance, while 20-30 mm crushed stone can increase the thickness and strength of the road surface. At the same time, the mixed use of crushed stones of different particle sizes can form a more uniform mixture and reduce the damage to the road surface caused by local stress concentration. This mixture can better resist the influence of vehicle load and natural environment and extend the service life of the road surface.
[0028] The present invention also provides a construction method for a siliceous slag mixture for a road surface base, the construction method comprising: performing two-stage mixing, paving, rolling and curing on the siliceous slag mixture.
[0029] A1. Two-stage mixing
[0030] In the present invention, due to the physical property of siliceous slag that it is easy to agglomerate and clump, a two-stage mixing production process is adopted when mixing the mixed material.
[0031] Specifically, the siliceous slag mixture enters two mixing tanks connected in series in sequence and is mixed in the mixing tanks. Here, the two-stage mixing uses two mixing tanks connected in series, thereby avoiding the problem that one mixing tank cannot mix the siliceous slag evenly.
[0032] Optionally, the mixing time is not less than 15 seconds to ensure that the mixture is mixed evenly. Preferably, a vibration mixing technology is used. It should be noted that after mixing, the white material needs to be re-mixed. When encountering serious wall sticking problems, it is necessary to clean and hit the siliceous slag mixture to knock off the sticking wall.
[0033] A2. Paving steps:
[0034] In one embodiment, paving is performed using a crawler-type hydraulic fully automatic paver.
[0035] Specifically, the crawler hydraulic fully automatic paver should be equipped with an automatic leveling system and measures to prevent material segregation.
[0036] Specifically, the middle of the auger of the paver is equipped with a reverse blade to reduce longitudinal segregation. The auger should be equipped with a rubber front baffle to reduce vertical segregation during paving.
[0037] Specifically, a rubber baffle is installed in front of the paver scraper (including the widened side plate), and the height of the bottom of the rubber baffle from the top surface of the underlying layer should be no more than 10 mm.
[0038] Specifically, during the paving process, the paver has a vibrator and a rammer. The vibration frequency of the vibrator shall not be less than 30Hz, the impact frequency of the rammer shall not be less than 20Hz, and the stroke shall not be less than 6mm.
[0039] In one embodiment, the paving step includes: paving the mixture after the two-stage mixing by a paver, wherein the paving speed is 1.0 to 3.0 m / min.
[0040] Specific:
[0041] (1) During the paving process, the speed of the paver should be kept uniform and constant, and the paving speed of the mixture should be controlled at 1.0 to 3.0 m / min.
[0042] (2) When paving the mixture, it should be kept continuous. If the interruption time exceeds 2 hours due to some reason, transverse joints should be provided.
[0043] (3) Avoid longitudinal joints during paving. When paving in two sections, the longitudinal joints should be rolled more tightly. When longitudinal joints exist, they should be connected vertically. Slanting is strictly prohibited. When using multiple pavers for paving, the models and degree of wear of the pavers should be the same. During construction, the front and rear spacing of the pavers should not exceed 10m, and the adjacent construction sections should overlap by 30cm to 40cm in the longitudinal direction.
[0044] (4) When the single-operation width of the stable layer is 11 to 12 m, the length of each flow operation section is 300 m; when the single-operation width of the stable layer is greater than 12 m, the length of the operation section is shortened accordingly.
[0045] (5) A dedicated person should be assigned behind the paver to eliminate aggregate segregation and agglomeration, promptly remove segregated or agglomerated areas, and fill them with good mixed materials.
[0046] (6) For extra-wide road sections that cannot be paved mechanically, manual paving, trimming and rolling should be used simultaneously.
[0047] (7) Paving surplus and mixed materials lost on site should be collected and disposed of in a centralized manner and must not be discarded at will.
[0048] Here, when the present invention adopts two layers of continuous paving, when the quality of the lower layer has problems, the upper layer should be processed at the same time. Before the construction of the upper structure, the maintenance materials used in the lower layer should be thoroughly cleaned, and after the construction quality of the lower bearing layer is tested to be qualified, the upper structure layer can be paved.
[0049] A3. Rolling steps:
[0050] In one embodiment, the rolling step includes: rolling the paved mixture through double steel wheels, single steel wheels, and rubber wheels in sequence.
[0051] Specific:
[0052] (1) First, double steel wheels are used for rolling; during the rolling process, the double steel wheels do not vibrate when moving forward, and vibrate when moving backward;
[0053] (2) secondly, a single steel wheel is used for rolling, during which the single steel wheel is vibrated;
[0054] (3) Rub and rub the rubber wheel countless times, and the rubber wheel should be larger than 30t;
[0055] (4) Finally, double steel wheels are used for finishing.
[0056] In one embodiment, the pressing should follow the principle of first the outside and then the inside. The outside rolling should exceed the paving surface by more than 10 cm, the longitudinal direction should be serrated (minimum staggered 0.5m), and the pressing joints should be staggered in a step-like manner horizontally.
[0057] In one embodiment, a dedicated person should be assigned to direct the rolling process to prevent leakage and wheel marks. When soft and elastic phenomena occur, the mixed material in that part should be dug out in time, and the roadbed material with a moisture content that meets the design requirements should be replaced for rolling. An appropriate amount of coarse aggregate or cement can also be added and mixed evenly before compaction.
[0058] In one embodiment, during construction in hot summer weather, if the roadbed material becomes loose or shifts during the rolling process, it should be moistened by spraying water mist and stirred evenly to adjust its moisture content to the moisture content at the factory.
[0059] In one embodiment, a side form is set and fixed during rolling, and a small roller and a plate compactor are used to perform initial compaction near the form on both sides of the roadbed, and then a double steel wheel roller and a rubber wheel roller are used for compaction. Within a 30cm range of facilities such as inspection wells and curbstones, large rollers are not easy to compact, so a high-power plate compactor combined with a small roller can be used for compaction.
[0060] A4. Health care steps:
[0061] After the siliceous slag pavement base material layer is rolled and passed the compaction inspection, it should be covered and cured within 2 hours. The construction unit should choose the appropriate curing method based on the actual situation of the project site, which can be covered with film, impermeable geotextile, wet sand, asphalt emulsion, or watering with a sprinkler truck.
[0062] For example, watering for curing: the number of watering times per day should depend on the climate. During construction during high temperature periods, water should be sprinkled twice in the morning and afternoon. During the curing period, care should be taken to keep the surface of the stabilizing material moist at all times.
[0063] For example, film covering and curing: (1) When the weather is hot and dry, the surface moisture of the siliceous slag base layer should be observed before covering the film. If necessary, appropriate spraying and watering can be applied, but the surface of the stabilizing layer should not be eroded. Keep the base layer moist and do not allow the base layer to frequently alternate between dry and wet. (2) For areas with large evaporation or projects with a curing time of more than 15 days, appropriate watering should be applied during the curing process. (3) The films should be overlapped intact to avoid leaks. After the film is covered, sand and other materials should be used to form a grid-like cover. If the film is partially damaged, it should be replaced in time. (4) The film can be lifted only after curing for 1 to 2 days before the construction of the upper structure layer.
[0064] For example, geotextile maintenance: (1) Use permeable geotextile to cover the entire section of the stable material layer, or waterproof geotextile can be laid. (2) During the laying process, attention should be paid to the overlap between the seams, and no gaps should be left. (3) After laying the geotextile, attention should be paid to watering. The number of watering per day should depend on the climate. During construction during high temperature periods, water should be sprinkled once in the morning and once in the afternoon.
[0065] In one embodiment, the curing time should be no less than 7 days. When the average daily temperature is below 10°C, the curing time should be extended to 14 days in adverse weather conditions such as rainy season, and the total curing period should be extended to 2 days before the construction of the upper layer. Except for sprinkler trucks and small commuter vehicles, no vehicles are allowed to pass during this period, and crawler engineering vehicles are strictly prohibited from directly pressing.
[0066] In one embodiment, when cracks appear in the base layer during the curing process, after deflection detection, if the bearing capacity of the structural layer meets the design requirements, the asphalt surface layer above can be paved, or the cracks can be treated by filling the cracks. For example, filling the cracks; laying glass fiber grids or single-sided singed polypropylene anti-cracking base fabrics at the cracks; laying hot modified asphalt.
[0067] The present invention is described in detail below by way of examples and experimental examples, but these are merely examples and do not limit the present invention in any form.
[0068] Siliceous slag addition and material ratio
[0069] Siliceous slag is used as a stabilized material and is added to the cement stabilized crushed stone mixture in the form of replacing fine aggregates by equal mass. The siliceous slag content of Comparative Example 1 is 50%, and the siliceous slag content of Example 1 is 38%. The proportions of each material are shown in Table 1.
[0070] Table 1 Siliceous slag addition and material ratio
[0071]
[0072] Result analysis:
[0073] (1) Compressive strength test results and analysis
[0074] Table 2 Compressive strength test results
[0075]
[0076] As shown in Table 2, the siliceous slag pavement base specimens before adjusting the mix ratio were easy to fall off during molding, and the 7-day unconfined compressive strength was less than 2MPa, which did not meet the pavement base strength requirements; after adjusting the mix ratio, the 7-day unconfined compressive strength was 3.5MPa~6MPa, and the strength increased by nearly 3 times, meeting the pavement base strength requirements for expressways / first-class highways, as well as second-class highways / below second-class highways with heavy traffic.
[0077] (2) Water stability
[0078] Water stability refers to the ability of the base structure to maintain good compressive strength when subjected to the shrinkage-swelling cycle or full immersion of water, also known as the water resistance of the pavement base. The base structure mixed with siliceous slag should also have good water stability, that is, water entering from the road surface or infiltrating into the base from the roadbed should not cause a significant decrease in the integrity and compressive strength of the base structure, whether in the case of shrinkage-swelling reciprocating cycle or in the case of long-term full immersion. Water stability is expressed by the water stability coefficient, that is, the ratio of the water immersion strength to the strength under standard maintenance conditions. The larger the water stability coefficient, the better the water stability of the material.
[0079] For water stability under dry-wet cycle conditions, according to the test method T 0843-2009 in the Test Code for Stabilized Materials of Inorganic Binders for Highway Engineering (JTG E51-2009), cylindrical specimens with a diameter and height of 150 mm were formed. After standard curing for 27 days, they were immersed in water for 1 day, and the surface moisture of the specimens was wiped dry with a wet cloth after being taken out. Then, one group of specimens was taken for unconfined compressive strength test under non-dry-wet conditions. At the same time, a group of specimens that needed to be subjected to dry-wet cycles were first placed in a 60℃±1℃ forced air drying oven for 8 hours, and then taken out and immersed in a 20℃ water tank for 16 hours. This was one dry-wet cycle. After 5 dry-wet cycles, the unconfined compressive strength of the specimens after the dry-wet cycles was tested.
[0080] For water stability under full immersion conditions, according to the test method T 0843-2009 in the Test Code for Stabilized Materials of Inorganic Binders for Highway Engineering (JTGE51-2009), cylindrical specimens with a diameter and height of 150 mm were formed. After standard curing for 27 days, they were immersed in water for 1 day. After being taken out, the moisture on the surface of the specimens was wiped dry with a wet cloth; then, one group of specimens was taken for unconfined compressive strength test under non-continuous immersion conditions, and at the same time, a group of specimens that needed to be immersed for another 5 days were taken and placed in a 20℃ water tank. After the 5-day immersion, the unconfined compressive strength of the specimens was tested.
[0081] The test data are shown in Table 3.
[0082] Table 3 Results of water stability test of siliceous slag pavement base material at 28 days
[0083]
[0084] It can be seen from Table 3 that the water stability coefficient of the pavement base material after adding siliceous slag is slightly better than that of the cement-stabilized macadam pavement base material, indicating that the water stability is good. It is estimated that the water stability performance of the traditional cement-stabilized macadam pavement base can be achieved in actual construction.
[0085] (3) Flushing performance
[0086] When a vehicle passes by the road, the dynamic load can generate pore water pressure on the road surface structure, and this water pressure is high enough to produce a scouring effect on the base material. Repeated scouring will take away part of the base material, and finally form slurry pumping through the existing cracks in the road surface. Therefore, it is necessary to test the scouring performance of the base material. The test data is shown in Table 4.
[0087] Table 4 Scour test results of siliceous slag pavement base at 28 days
[0088]
[0089] It can be seen that the scouring mass loss rate of siliceous slag pavement base material is basically the same as that of ordinary cement-stabilized gravel pavement base material, and it has a good ability to resist dynamic water scouring. It is estimated that in actual construction, it can achieve the scouring resistance performance of traditional cement-stabilized gravel pavement base material.
[0090] (4) Environmental risk assessment
[0091] Comparison table 5 between the pollutant test report of siliceous slag raw materials and the current specifications:
[0092] Table 5 Siliceous slag pollutant detection report
[0093]
[0094]
[0095] It can be seen that the leaching liquid of siliceous slag raw materials meets the four standard limits of the "Groundwater Quality Standard" (GB / T 14848-2017), and the environmental risks are controllable after being made into pavement base materials.
[0096] In summary:
[0097] (1) Siliceous slag raw materials: fine particle size, 100% pass rate of 2.36mm sieve hole; not easy to expand in water; activity coefficient 48.79%, mainly used as inert filler in road base materials.
[0098] (2) (10% moisture content) Siliceous slag-based pavement base material: The optimum moisture content is 6%; the 7-day unconfined compressive strength is 3.5 MPa to 6 MPa, which meets the pavement base strength requirements for medium and light traffic on expressways / first-class highways and heavy traffic on second-class / second-class and below highways, and meets all subbase strength requirements; the 28-day water stability coefficient after 5 dry-wet cycles is 111%, and the 28-day water stability coefficient after 5 days of full immersion is 109%, which is basically the same as the water stability of ordinary water-stabilized layers; the scour mass loss is 0.165%, and the scour resistance is basically the same as that of ordinary water-stabilized layers; the residual compressive strength ratio after freeze-thaw is 107%, which has strong frost resistance; when designing the pavement, it is necessary to combine the splitting strength of the siliceous slag pavement base material to verify the tensile stress at the bottom of the pavement base layer.
[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A siliceous slag mixture for road surface base, characterized in that: The siliceous slag mixture comprises siliceous slag, crushed stone and cement-based composite cementitious material; wherein the cement-based composite cementitious material comprises cement, coal furnace slag from a thermal power plant and limestone powder.
2. The siliceous slag mixture according to claim 1, characterized in that: The mass ratio of the siliceous slag, crushed stone and cement-based composite cementitious material is 35-40:55-60:5-10.
3. The siliceous slag mixture according to claim 1, characterized in that: The mass ratio of the cement, coal furnace slag from thermal power plants and limestone powder is 2-3:1:2-3.
4. The siliceous slag mixture according to claim 1, characterized in that: The crushed stones have three particle sizes, including 5-10 mm, 10-20 mm and 20-30 mm.
5. The siliceous slag mixture according to claim 4, characterized in that: The mass ratio of the 5-10 mm crushed stone, the 10-20 mm crushed stone and the 20-30 mm crushed stone is 5-10:40-45:5-10.
6. The construction method for a road surface base according to any one of claims 1 to 5, characterized in that: The construction method comprises: The siliceous slag mixture is mixed, spread, rolled and cured in two stages.
7. The construction method according to claim 6, characterized in that: The two-stage mixing step comprises: The siliceous slag mixture enters two mixing tanks connected in series in sequence and is mixed in the mixing tanks for a mixing time of not less than 15 seconds.
8. The construction method according to claim 6, characterized in that: The paving steps include: The mixture after two-stage mixing is spread by a paver, wherein the spreading speed is 1.0-3.0 m / min, the vibration frequency of the vibrator in the paver shall not be lower than 30 Hz, the impact frequency of the rammer shall not be lower than 20 Hz, and the stroke shall not be lower than 6 mm.
9. The construction method according to claim 6, characterized in that: The rolling step comprises: The paved mixture is rolled once with double steel wheels; during the rolling process, the double steel wheels do not vibrate when moving forward, and vibrate when moving backward; A single steel wheel is used for rolling once, during which the single steel wheel vibrates; Use rubber wheels for kneading and rubbing, and the rubber wheels are larger than 30t; Double steel wheels are used for finishing.
10. The construction method according to claim 6, characterized in that: The curing is carried out by film covering or geotextile curing, and the curing time is not less than 7 days.
Citation Information
Patent Citations
Process for producing cement by hypercalcium powdered coal ash
CN1012951B
Stabilizing material as well as preparation method and application thereof
CN107572931A